Raver1 links Ripk1 RNA splicing to caspase-8-mediated pyroptotic cell death, inflammation, and pathogen resistance - Boyao Zhang; Pontus Orning; Jesse W. Lehman; Alexandre Dinis; Leslie Torres-Ulloa; Roland Elling; Michelle A. Kelliher; John Bertin; Megan K. Proulx; Jon D. Goguen; Liv Ryan; Richard K. Kandasamy; et al. (Proceedings of the National Academy of Sciences, 2025)
Multiple cell death and inflammatory signaling pathways converge on two critical factors: receptor-interacting serine/threonine kinase 1 (RIPK1) and caspase-8. Careful regulation of these molecules is critical to control apoptosis, pyroptosis, and inflammation. Here, we found a pivotal role of Raver1 as an essential regulator of Ripk1 pre-mRNA splicing, expression, and functionality and the subsequent caspase-8-dependent inflammatory cell death. We show that Raver1 influences mRNA diversity primarily by repressing alternative exon inclusion. Macrophages from Raver1 -deficient mice exhibit altered splicing of Ripk1 . As a result, Raver1 -deficient primary macrophages display diminished cell death and decreased interleukin-18 and interleukin-1ß production, when infected with Yersinia bacteria, or by restraining TGF-ß-activated kinase 1 or IKKβ in the presence of lipopolysaccharide, tumor necrosis factor family members, or interferon-γ. These responses are accompanied by reduced activation of caspase-8, Gasdermin D and E, and caspase-1 in the absence of Raver1 . Consequently, Raver1 -deficient mice showed heightened susceptibility to Yersinia infection. Raver1 and RIPK1 also controlled the expression and function of the C-type lectin receptor Mincle. Our study underscores the critical regulatory role of Raver1 in modulating innate immune responses and highlights its significance in directing in vivo and in vitro inflammatory processes.